Charging activation and desulfurization of MnS unlock the active sites and electrochemical reactivity for Zn-ion batteries. (September 2020) - Chen, Xiujuan; Li, Wei; Xu, Yaobin; Zeng, Zhipeng; Tian, Hanchen; Velayutham, Murugesan; Shi, Wangying; Li, Wenyuan; Wang, Chongmin; Reed, David; Khramtsov, Valery V.; Li, Xiaolin; et al.
Abstract: The rechargeable aqueous zinc-ion batteries (ZIBs) based on the Zn/MnO2 couple and mildly acidic electrolyte have emerged as promising large-scale energy storage systems. This work reports an in situ electrochemical activation approach to oxidizing MnS into an electrochemically derived oxide (MnS-EDO), which unlocks its potential as high-performance cathodes for ZIBs. MnS-EDO contains fragmented layers with abundant defects and thus demonstrates large electrochemically active surface areas, high electrochemical reactivity, fast ion diffusion kinetics, accelerated charge transfer and exceptional structural robustness during cycling compared to α-MnO2 . MnS-EDO exhibits a specific capacity of 335.7 mAh g −1 with ~100% capacity retention after 100 cycles at 0.3 A g −1, outstanding rate capability and long-term stability retaining 104 mAh g −1 after 4000 cycles at 3 A g −1 . This work elucidates the underlying electrochemical insights and a hybrid discharge mechanism involving homogeneous Zn 2+ intercalation at ~1.4 V and subsequent heterogeneous reactions of insertion of both H + and Zn 2+ at ~1.25 V. The ambiguities among Zn buserite, birnessite and zinc hydroxide sulfate are clarified. This work provides a simple and low-cost approach to unlocking the potential of MnS-EDO cathode for promising aqueous rechargeable ZIBs and sheds light on a mechanistic understanding of manganese oxide-based cathodes. Graphical abstract: Image 1 Highlights: In-situ electrochemical activation unlocks MnS potential as an advanced ZIB cathode. Electrochemically derived MnS-EDO features abundant defects, vacancies and electrochemically active sites. Superior reactivity and kinetics of MnS-EDO contribute to high-performance ZIBs. Insights into mechanistic understanding of Mn-based cathodes have been clarified.